Subfatin and asprosin, two new metabolic players of polycystic ovary syndrome - Deniz, Rulin; Yavuzkir, Seyda; Ugur, Kader; Ustebay, Dondu Ulker; Baykus, Yakup; Ustebay, Sefer; Aydin, Suleyman (Taylor & Francis Inc, 2021)
Asprosin and subfatin are recently discovered two new hormones of adipocyte origin that play a role in the regulation of glucose metabolism. Polycystic ovary syndrome (PCOS) is a gynaecological syndrome presenting with energy turbulence. The aim of this study was to investigate whether asprosin and subfatin play a role in PCOS disease. Thirty participants with a diagnosis of PCOS and thirty control group participants were included in this case-control study. Hormone profiles of the participants (subfatin, asprosin, insulin, prolactin, thyroid-stimulating hormone (TSH), oestradiol (E2), follicle-stimulating hormone (FSH), luteinising hormone (LH), dehydroepiandrosterone sulphate (DHEA-SO4), lipid profiles [(total testosterone, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglyceride, cholesterol)], fasting blood sugar (FBS) and high-sensitivity C-reactive protein (hs-CRP) values were measured. While the levels of asprosin, LDL and triglyceride, TSH, E2, FSH, LH, DHEA-SO(4)were found to be significantly higher in patients with PCOS compared to controls (p = .005;p = .01), subfatin and HDL levels were found to be low. Significantly decreasing subfatin and increasing asprosin levels in circulation in PCOS may play a role in the etiopathology of this disease and that they may also be new candidate molecules in addition to classical laboratory parameters in the diagnosis and follow-up of PCOS in the future.Impact statement What is already known on this subject?The studies investigating the relationship between PCOS and asprosin are contradictory. Although subfatin has been studied in many metabolic diseases, it has not been studied yet whether it is associated with PCOS. Furthermore, whether there is a mutual relationship between subfatin and asprosin in patients with PCOS has not been studied yet. What do the results of this study add?This available data indicates that significantly decreasing subfatin and increasing asprosin levels in the circulation in PCOS may play a role in the etiopathology of this disease. What are the implications of these findings for clinical practice and/or further research?The findings are promising in that decreasing subfatin and increasing asprosin levels will shed new light on reproductive endocrinology changes caused by PCOS and may help to clarify the pathophysiology of PCOS. Furthermore, in our study, the asprosin/subfatin ratio was above three in PCOS disease. This ratio reported here is anticipated to contribute to the course or follow-up of the disease in the future. Also, subfatin has been investigated here for the first time, may also be a new candidate molecule in addition to classical laboratory parameters in the diagnosis and follow-up of PCOS.
Keywords: Subfatin; asprosin; metabolic players; high-sensitivity C-reactive protein; polycystic ovary syndrome